Local Communities Attitudes Towards Participatory Forest Management Approach and its Implications for Sustainability of Forest Condition and Livelihoods - Saguye, Tesfaye Samuel (American Journal of Human Ecology, 2017)
This study assess the local communities perceptions of and attitudes towards participatory forest management approaches in the Chilim—Gaji forest in Ethiopia and further analyses factors that affect attitudes towards the forest and forest management. Data for the study was generated through household survey comprising of 265 respondents selected through simple random technique and substantiated by key informant interview and FGDs. Data analyzed by employing both descriptive and inferential statistics. The study findings revealed that, generally the respondents held positive attitudes towards the forest and PFM approach. The results also depicted the association between socio-economic features of people living close to the forest and their use of forest resources and demonstrated the basis of attitudes towards those managing the forest. Sixty percent of respondents were found to agree with the idea of Chilimo-Gaji forest conservation; however, statistically significant differences were found between the villages in terms of supportive attitudes toward the forest conservation system (p = 0.02) and toward the PFM System (p = 0.01). However, those highly dependent on the forest to generate income remained reluctant and unsupportive, suggesting that high levels of support toward a conservation project by sections of the community may not translate into conservation success, because the drivers of the deforestation and forest degradation are not supportive. Regression results showed that these perceptions were influenced by different socio-economic, demographic and geophysical factors. These factors included: membership in social groups, wealth stratums, farm size, , livestock ownership and dependency on forest for extraction. A direct financial benefit accrues from the PFM system was found to be the main factor of the respondents’ attitudes and perceptions.